The Evolution of the Coloring System in the Ornamental Carvings of Istano Basa Pagaruyung - shintia shintia; Mutia Budhi Utami; Armen Nazaruddin; Yunis Muler (Institut Seni Indonesia Padang Panjang, 2026)
The carvings of Istano Basa Pagaruyung are an important part of Minangkabau cultural heritage, embodying philosophical values and cultural identity. Traditionally, their coloring system relied on natural pigments obtained from the surrounding environment. However, these materials have gradually been replaced by synthetic dyes. This study aims to examine the transformation of the coloring system in Istano Basa Pagaruyung carvings, identify the factors driving this change, and analyze its implications for the preservation of Minangkabau cultural values. A qualitative descriptive approach was employed, with data collected through observation, interviews, documentation, and literature review. The findings indicate that the shift from natural to synthetic dyes has been influenced by the limited availability of natural materials, easier access to synthetic alternatives, greater efficiency, and the practical needs of building maintenance. Despite changes in the coloring materials, the traditional color scheme and its symbolic meanings have been preserved. This demonstrates that the transformation represents an adaptive response to contemporary conditions without compromising the cultural values embodied in the carvings. The findings reflect the Minangkabau philosophy â€œBolehlah beranjak duduk, tetapi tikarnya itu juga,â€ which emphasizes that adaptation may occur while fundamental cultural values remain intact. This study contributes to the preservation of traditional carving art as a significant component of Minangkabau cultural heritage.